1D Energetic Metal‐Organic Framework: Sodium 6‐Nitro‐5‐oxidopyrazolo[3, 4‐c][1, 2, 5]oxadiazol‐4‐ide with Good Thermal Stability. Issue 17 (13th June 2017) - Yu, Qiong; Yang, Hongwei; Ju, Xuehai; Lu, Chunxu; Lin, Qiuhan; Zhang, Jiaheng; Cheng, Guangbin
Abstract: A ladder‐like 1D energetic metal‐organic framework, sodium 6‐nitro‐5‐oxidopyrazolo[3, 4‐c][1, 2, 5]oxadiazol‐4‐ide was first synthesized from the potassium salt. The sodium salt with an interesting furazan‐pyrazole system which is first synthesized by an intramolecular condensation, is fully characterized by crystal X‐ray diffraction, elemental analysis, IR spectroscopy. The sodium salt shows a density of 1.88 g cm −3, a high decomposition temperature of 258 o C, and a promising calculated detonation velocity of 7760 m s −1 . It has an impact sensitivity of 16 J which makes it a replacement as a thermally stable energetic material. Besides, the natural compound 6‐nitro‐4H‐pyrazolo[3, 4‐c][1, 2, 5]oxadiazole 5‐oxide shows the best energetic properties with calculated detonation velocity of 9407 m s −1 and calculated detonation pressure of 40.4 GPa. Abstract : A ladder–like 1D energetic metal–organic framework: sodium 6‐nitro‐5‐oxidopyrazolo[3, 4‐c][1, 2, 5]oxadiazol −4‐ide was first synthesizedand characterized by single‐crystal X‐ray diffraction. Owing to the 1D metal‐organic framework, it showsgood thermal stability and relative low sensitivities. Furthermore, it exhibits acceptable detonation properities which make ita promising potential candidate of new thermally stable energetic materials.Introduction